Synthesis of novel triazole-incorporated isatin derivatives as antifungal, antitubercular, and antioxidant agents and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nawale, Laxman; Arkile, Manisha A.; Sarkar, Dhiman; Shingate, Bapurao B. (Journal of Heterocyclic Chemistry, 2017)
A library of 1,2,3-triazoles efficiently prepared via click chemistry and evaluated for their antifungal, antitubercular, antioxidant, cytotoxicity, molecular docking and ADME prediction.